Analisa Kepuasan Pengguna E-Learning Universitas Sepuluh Nopember Papua Menggunakan Metode Servqual - Bahar, Dimas Adhitya; Sutejo, Heru; Tatuhey, Emy L. (STMIK Banjarbaru, 2024)
Sepuluh Nopember University Papua implements an e-learning system to support learning. The quality of e-learning services is measured using the SERVQUAL method to identify gaps between user perceptions and expectations. This research aims to measure the quality of USN Papua's current e-learning services and become an important reference for USN Papua in making improvements and improving the quality of e-learning services in the future. The SERVQUAL method used in this research has five measurement dimensions, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy. This research focuses on the Gap 5 dimension, namely identifying the gap between user perceptions and expectations of USN Papua e-learning services. The results of this research found that USN Papua e-learning users were still